2013
DOI: 10.6002/ect.2012.0223
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting Pediatric Deceased-Donor Kidneys Into Adult Recipients: An Iranian Experience

Abstract: Objectives: This study sought to evaluate graft outcome of kidneys from deceased-donor pediatric donors in adult recipients, and compare it with outcomes of kidney transplants from adult donors. Materials and Methods: This historical cohort study involved 2 groups. Group 1 included 23 first kidney adult recipients who received their first renal transplant from pediatric deceased-donor donors. Group 2 consisted of 33 first renal transplant adult recipients with kidneys coming from adult deceased donors. The Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies examining outcomes following transplantation using SPDs (with more than 20 recipients) are shown in Table 2 [5, 1115, 18, 20, 22, 23, 2528, 30, 31]. In one of the largest studies to date, a US-based registry analysis of 2449 renal transplants from paediatric donors under 20 kg [11], the authors demonstrated a 5-year graft survival rate of 55% for single-organ kidney transplants and 73% for en bloc kidney (EBK) transplants, with a hazard ratio of 0.96 per 1 kg increase in donor weight for graft loss.…”
Section: Graft Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining outcomes following transplantation using SPDs (with more than 20 recipients) are shown in Table 2 [5, 1115, 18, 20, 22, 23, 2528, 30, 31]. In one of the largest studies to date, a US-based registry analysis of 2449 renal transplants from paediatric donors under 20 kg [11], the authors demonstrated a 5-year graft survival rate of 55% for single-organ kidney transplants and 73% for en bloc kidney (EBK) transplants, with a hazard ratio of 0.96 per 1 kg increase in donor weight for graft loss.…”
Section: Graft Survivalmentioning
confidence: 99%
“…Median 9 years. PS 100%▪ SOK + EBK – 83%Bretan [25]1993–1996400–5 years1-year graft survivalGT rate 2.5%▪ EBK – 100%2-year graft survival▪ EBK – 85%Sui [26]2012–201438< 15 kg1-year graft survivalAll into paediatric recipients▪ All SPD organs – 89%▪ SOK – 96%▪ EBK – 70%Basiri [27]2006–201336Not defined1-year graft survivalGT rate 5.5%▪ EBK + SOK – 90%▪ Adult DD – 92%Hobart [28]1990–199733< 4 years1-year graft survivalGT rate 15%▪ EBK – 87%▪ Adult DD – 84%Mohanka [29]2002–200633< 15 kg1-year graft survivalAll into adult recipients▪ SOK – 86%▪ EBK – 79%Salvatierra [30]1969–1973321–9 years6-month graft survival▪ SOK – 50%Zafarghandi [31]2004–200923< 16 years1-year graft survivalAll into adult recipients▪ EBK + SOK – 96%▪ Adult DD – 91%5-year graft survival▪ EBK + SOK – 85%▪ Adult DD – 85% GS graft survival, GT graft thrombosis, HR hazard ratio, GL graft loss, LD live donor, DD deceased donor, SOK single organ kidney, EBK en bloc kidney, PS patient survival…”
Section: Graft Survivalmentioning
confidence: 99%